2017
DOI: 10.3311/ppme.9212
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Mechanical Behavior and Fatigue in a Weld Bead by Friction Stir for a 6082-T6 Aluminum Alloy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…From this perspective, the longitudinal stress results in the numerical study shown in the Figs. (10,11,12,13), are comparable to the micro-hardness results, obtained by GHAZI [3]. The inverse relationship is shown in Fig.…”
Section: Comparison With the Validation Study: Stress -Microhardness Relationshipsupporting
confidence: 86%
See 1 more Smart Citation
“…From this perspective, the longitudinal stress results in the numerical study shown in the Figs. (10,11,12,13), are comparable to the micro-hardness results, obtained by GHAZI [3]. The inverse relationship is shown in Fig.…”
Section: Comparison With the Validation Study: Stress -Microhardness Relationshipsupporting
confidence: 86%
“…There are the nugget region, the thermo-mechanically affected zone TMAZ and the heat affected zone HAZ. Each region has qualitatively or quantitively distinct values of microstructure, hardness and residual stress [11].…”
Section: Influence Of Welding Speed On Longitudinal Residual Stressmentioning
confidence: 99%
“…In general, fatigue behavior of welded materials is complicated by large variation in nature and properties of materials, presence of geometric defects and many factors intrinsic (inclusions, lack of penetration, gas pore), etc. [2][3][4][5][6][7][8]. Many studies show that, from such defects, the stage of initiation of the fatigue crack can be reduced [9] and that consequently a large part of the life of the welded joints subjected to fatigue propagation occurs [10].…”
Section: Introductionmentioning
confidence: 99%
“…a/W=0.3 a/W=0.5 a/W=0.7 Also for welded specimens (Figure 12), it is noticed a high difference for stress intensity factor KI in function of loading angles and ratio a/W. This is attributed to the level of compressive residual stress at the nugget comparatively to Heat Affected Zone or base metal (i.e., Low micro hardness in nugget zone) [30,31] and the calculation in taking out of the empirical stress intensity factor compared to the numerical results using J-integral contour.…”
Section: Stress Intensity Factorsmentioning
confidence: 90%